Save planet earth: SOS in extreme danger - Sen, Benita (New Delhi The Energy and Resource Institute, 2013)
One type of living being is disappearing from the face of this earth every sevenminutes. Species that have survived millennia are dying out, and these may include many we haven't even discovered yet! SOS: In Extreme Danger reveals the most critically endangered plants andanimals in the world as well as places and cultures in danger due to climate change. Answer the distress call. Act now to save the earth!
Keywords: Save Planet Earth